Preparation method of lithium iron phosphate positive electrode and battery with quantitatively regulated xrd diffraction characteristics

CN122992001APending Publication Date: 2026-10-27SHENZHEN WARRANT NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611298001.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明提供了一种定量调控XRD衍射特征的磷酸铁锂正极及电池制备方法,克服现有掺杂改性不可定量、晶格结构调控无序、晶粒尺寸无法协同优化的缺陷,以XRD衍射角偏移量、特征峰半峰宽为核心量化结构指标,定向调控晶格晶面间距、晶粒尺寸与晶格微观应变,同步拓宽锂离子传输通道、提升橄榄石骨架结构稳定性,实现材料倍率性能与循环寿命协同提升

Benefits of technology

相较于未掺杂纯磷酸铁锂与常规无量化调控掺杂磷酸铁锂,本发明通过定量控制XRD 衍射角偏移量及半峰宽,带来如下突出技术效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992001A_ABST
    Figure CN122992001A_ABST
Patent Text Reader

Abstract

The application relates to a lithium iron phosphate positive electrode and a battery preparation method for quantitatively regulating XRD diffraction characteristics, and belongs to the technical field of lithium ion battery positive electrode materials. The application adopts LiFePO4 as a matrix, substitutes lithium sites with doped ions to form a single-phase solid solution, controls the offset amount Delta 2theta of the main characteristic peak diffraction angle of the (020) crystal face of XRD to be 0.10-0.25, controls the half-peak width of the (020) characteristic peak to be 0.135-0.170, and controls the grain size to be 51-80 nm; and the total molar content of the doped ions is 0.005-0.05. The application uses the XRD diffraction angle and the half-peak width as double quantitative scales to directionally regulate the crystal face spacing and the grain size, controllably offsets the diffraction peak by a small range, optimizes the lithium ion transmission channel and the crystal lattice skeleton stability, limits the half-peak width interval, and simultaneously considers the high order degree of the crystal and the short ion diffusion path. The above XRD structure characteristics are precisely reproduced through solid-phase uniform mixing and sectional temperature control sintering, the prepared material has strong electronic conductivity, excellent rate performance and good long cycle stability, the preparation process is suitable for the existing mass production line, and the material is suitable for power lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a lithium iron phosphate cathode and battery preparation method with quantitative control of XRD diffraction characteristics. Background Technology

[0002] Lithium iron phosphate (LFP) suffers from poor conductivity and slow ion migration due to its crystal structure, which significantly limits the improvement of its electrochemical performance. Because of its low ion diffusion rate, the diffusion ability of lithium ions within the active electrode material decreases even more significantly at low temperatures, leading to increased charge transfer impedance. In sub-zero temperatures, the energy density of LFP batteries decreases, significantly reducing the all-electric driving range of hybrid electric vehicles, shortening battery life, and increasing the operating cost of power batteries. The industry commonly uses metal ion doping to modify its crystal lattice, but a quantitative matching and control logic for doping elements, XRD diffraction angle shift, and characteristic peak full width at half maximum (FWHM) has not yet been established.

[0003] Existing doping modification techniques have significant shortcomings: First, there is no precise site occupancy control for doped ions. Ions randomly replace Fe or Li sites, resulting in uncontrollable lattice distortion. XRD characteristic diffraction peaks only undergo random shifts, making it impossible to achieve directional control of interplanar spacing. This can easily lead to excessive expansion or contraction of unit cells, exacerbating the dissolution of metal ions. Second, existing techniques only qualitatively describe the changes in half-peak width after doping. They have not established a synergistic quantitative control system for diffraction angle shift and diffraction peak half-peak width, and cannot simultaneously consider both grain size and lattice microstrain. If the full width at half maximum (FWHM) is too large, it indicates that the grains are small, the lattice disorder is high, the crystal integrity is poor, and the charge transfer impedance of the material is large. If the FWHM is too small, the grain size is too large, the lithium-ion diffusion path is longer, and the high-rate performance is severely degraded. Third, the existing doping process relies solely on experience to adjust the doping amount and sintering parameters. There is no precise control logic based on XRD diffraction characteristics. The diffraction peak shift and FWHM dispersion are large among different preparation batches, resulting in poor electrochemical performance repeatability. It is difficult to simultaneously achieve high capacity, excellent rate performance, and long-cycle stability. Summary of the Invention

[0004] This invention provides a method for quantitatively controlling the XRD diffraction characteristics of lithium iron phosphate cathodes and batteries, overcoming the shortcomings of existing doping modifications that cannot be quantitatively controlled, have disordered lattice structure control, and cannot synergistically optimize grain size. Using XRD diffraction angle shift and characteristic peak half-width as core quantitative structural indicators, it directionally controls the lattice interplanar spacing, grain size, and lattice microstrain, simultaneously widening lithium-ion transport channels and improving the stability of the olivine framework structure, thereby achieving a synergistic improvement in material rate performance and cycle life.

[0005] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate cathode with quantitatively controlled XRD diffraction characteristics, the method comprising the following steps: S11, according to the chemical formula Li x M y FePO4 is prepared by mixing lithium (Li), iron (Fe), phosphorus (P), carbon (C), and dopant element (M) in deionized water and grinding to obtain a slurry. The slurry is then dried and sintered in stages under an inert atmosphere. The sintered product is then sieved to obtain metal ion-doped lithium iron phosphate active material. Here, x ranges from 0.95 to 0.995, y ranges from 0.005 to 0.05, and the dopant element M is selected from one or more metal ions chosen from Ti, Mg, Zr, Cr, and Nb. S12. Mix the metal ion-doped lithium iron phosphate active material with binder and conductive agent evenly to prepare a positive electrode slurry. S13. The positive electrode slurry is coated on the surface of the current collector, and then dried and rolled to obtain a lithium iron phosphate positive electrode sheet.

[0006] A further technical solution is that, in the X-ray diffraction pattern of the metal ion-doped lithium iron phosphate active material, the offset Δ2θ of the (020) crystal plane corresponding to the 2 times diffraction angle is 0.10°~0.25°, and the full width at half maximum (FWHM) value of the (020) crystal plane is 0.135°~0.170°.

[0007] A further technical solution is that the relationship between the offset of twice the diffraction angle of the (020) crystal plane and the full width at half maximum (FWHM) value conforms to the first formula: S=Δ2θ×FWHM Where S ranges from 0.015 to 0.040, Δ2θ is the offset of twice the diffraction angle of the (020) crystal plane, and FWHM is the half-width at half maximum (WHM) value of the (020) crystal plane.

[0008] A further technical solution is that the iron source Fe is selected from one or more of ferric phosphate, ferric acetate, ferric oxide, ferric citrate, and ferrous oxalate; The phosphorus source P is selected from one or more of phosphoric acid, ammonium phosphate, and ammonium dihydrogen phosphate; The lithium source Li is selected from one or more of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate; The doping element source M is a compound containing at least one element selected from Ti, Mg, Zr, Cr, and Nb; The carbon source C is selected from one or more of glucose, sucrose, maltose, graphite, carbon nanotubes, graphene, and polyethylene glycol.

[0009] The further technical solution is that, in S11, the drying temperature is 60℃~120℃; the temperature of the low-temperature section of the sintering process is 350℃~420℃, the temperature of the high-temperature section is 620℃~700℃, and the sintering reaction time is 2h~8h.

[0010] A further technical solution is that the current collector is an aluminum foil.

[0011] A further technical solution is that the conductive agent is selected from one or more of carbon black, conductive graphite, carbon fiber, graphene, and carbon nanotubes.

[0012] Secondly, the present invention also provides a method for preparing a battery, the method comprising the following steps: S21. Mix the negative electrode active material with the binder and conductive agent evenly to prepare a negative electrode slurry; coat the negative electrode slurry onto the surface of the current collector, and then dry and roll-press it to obtain a negative electrode sheet. S22. The positive electrode sheet prepared by the method for preparing a doped lithium iron phosphate positive electrode with quantitative control of XRD diffraction characteristics as described in any of the above embodiments is assembled with the negative electrode sheet to form a battery cell. The battery cell is then hot-pressed and packaged to obtain a lithium-ion battery.

[0013] A further technical solution is that the negative electrode active material is selected from one of graphite, nano-silicon, and lithium titanate.

[0014] The further technical solution also includes testing steps for the resulting lithium-ion battery: S31. Charge at a preset rate with constant current until the charging cutoff voltage is reached, then switch to constant voltage charging. Let it stand after the charging current drops to the cutoff current. S32. Discharge at a constant current at a preset discharge rate until the discharge cutoff voltage is reached, then let stand still. S33. Repeat steps S31-S32 sequentially using multiple different discharge rates.

[0015] The technical solutions provided in the embodiments of the present invention have the following advantages compared with the prior art: Compared to undoped pure lithium iron phosphate and conventional uncontrolled doped lithium iron phosphate, this invention achieves the following outstanding technical effects by quantitatively controlling the XRD diffraction angle shift and full width at half maximum (FWHM): (1) Significant advantages of crystal structure The material of this invention is pure olivine single phase, without impurity phase diffraction peaks; (020) The characteristic peak Δ2θ is stably maintained at 0.10°~0.25°, and the cell parameters are adjustable and controllable; (020) The half width at half maximum is stably maintained at 0.135°~0.170°, and the grain size is 51~80 nm.

[0016] (2) The electrochemical performance is comprehensively improved. The first discharge specific capacity at 1C can reach more than 136 mAh / g, while the conventional doped material is only 133 mAh / g; the high rate capacity at 10C is 75 mAh / g, while the ordinary doped sample is only 65 mAh / g, which is suitable for the high energy density application requirements of power batteries.

[0017] (3) Strong industrial adaptability: This invention can accurately match the target XRD diffraction characteristics by simply adjusting the amount of doping, sintering temperature and holding time. It does not require complex equipment and post-processing. The raw materials are readily available and the process is simple. It can be directly adapted to existing lithium iron phosphate mass production lines, and the cost of large-scale production is low. Attached Figure Description

[0018] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 A schematic flowchart of a method for preparing a lithium iron phosphate cathode with quantitatively controlled XRD diffraction characteristics provided in an embodiment of the present invention; Figure 2 This is a schematic flowchart of a battery manufacturing method provided in an embodiment of the present invention; Figure 3 This is a schematic diagram of a sub-process of a battery manufacturing method provided in an embodiment of the present invention; Figure 4 A schematic diagram of powder resistance and rate capability parameters for an embodiment-comparative example provided for the present invention; Figure 5 A schematic diagram of the XRD (020) crystal plane lattice parameters of the embodiment-comparative example provided in this invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] See Figure 1 , Figure 1 This is a schematic flowchart illustrating a method for preparing a lithium iron phosphate cathode with quantitatively regulated XRD diffraction characteristics, provided in an embodiment of the present invention. The method includes the following steps S11-S13.

[0023] S11, according to the chemical formula Li x M y FePO4 is prepared by mixing lithium (Li), iron (Fe), phosphorus (P), carbon (C), and dopant element (M) in deionized water and grinding to obtain a mixed slurry. The mixed slurry is then dried and sintered in stages under an inert atmosphere. The sintered product is then sieved to obtain metal ion-doped lithium iron phosphate active material. The value of x ranges from 0.95 to 0.995, and the value of y ranges from 0.005 to 0.05. The dopant element M is selected from one or more metal ions chosen from Ti, Mg, Zr, Cr, and Nb.

[0024] S12, the metal ion-doped lithium iron phosphate active material is mixed evenly with binder and conductive agent to prepare positive electrode slurry.

[0025] S13. The positive electrode slurry is coated on the surface of the current collector, and then dried and rolled to obtain a lithium iron phosphate positive electrode sheet.

[0026] In this embodiment, the offset of the XRD (020) crystal plane diffraction angle and the half-peak width of the (020) crystal plane diffraction peak are used as dual quantitative control scales for doping modification. A complete correlation control mechanism of dopant ion occupancy, interplanar spacing (diffraction angle offset), grain microstrain (half-peak width), and electrochemical performance is established, which is different from the extensive modification approach of existing technologies that only qualitatively dopants without quantitative lattice constraints.

[0027] (1) (020) The directional shift of the diffraction angle of the crystal plane directly corresponds to the change in the interplanar spacing d, and the controllable shift range ensures linear fine adjustment of the cell parameters. When the diffraction peak shifts slightly to a higher angle, the cell shrinks slightly, the bond energy of the PO phosphate chemical bond increases, the rigidity of the crystal plane is enhanced during the charging and discharging process, and the long-term cycle stability is improved; when the diffraction peak shifts slightly to a lower angle, the interplanar spacing is moderately widened, the one-dimensional diffusion channel of lithium ions is widened, and the Li + The migration barrier is lowered, the lithium-ion diffusion coefficient is improved, and the high-rate discharge performance is significantly optimized.

[0028] (2) Achieving a synergistic balance between crystallinity and magnification in the half-width at half-maximum (WHM) quantitative range: The WHM of the diffraction peak is determined by both grain size and lattice microstrain. The 0.135°~0.170° WHM window of this invention has dual gains: a WHM below 0.170° indicates low lattice microstrain, high crystal order, significantly reduced charge transfer impedance, and improved electronic conductivity; a WHM above 0.135° ensures that the grains maintain a nanoscale, shortens the lithium-ion solid-phase diffusion distance, and avoids high-magnification polarization caused by micron-sized grains. Traditional doped materials cannot simultaneously meet both conditions, resulting in high powder resistance and poor magnification.

[0029] (3) The key innovation lies in the synergistic coupling of diffraction angle and full width at half maximum (FWHM). Simply controlling the diffraction angle shift without constraining the FWHM will result in numerous crystal defects or coarse grains; controlling only the FWHM without directional shifting of the diffraction peaks will not regulate the lithium-ion diffusion channels and framework stability. This invention simultaneously limits the coupling window of the two parameters Δ2θ and FWHM, achieving triple optimization of lattice channels, crystal integrity, and grain size, thus obtaining a comprehensive performance improvement that cannot be achieved by a single control, and possessing non-obviousness.

[0030] In a specific embodiment, taking the preparation of magnesium-doped lithium iron phosphate cathode as an example, the specific operation is as follows: Precursor liquid phase mixing: Lithium source, iron source, phosphorus source, carbon source and doped metal salt are simultaneously added to water and vigorously stirred to make the doped ions uniformly dispersed at the molecular scale. The composite precursor powder is then dried. By controlling the amount of doped salt added, the basic amplitude of lattice distortion is predetermined, and the diffraction angle shift range is locked.

[0031] Low-temperature pre-crystallization nucleation treatment: The precursor powder is pre-calcined at 350~420 ℃ for 2~3 h under a protective atmosphere to initially form olivine crystal nuclei, pre-regulate the basic size of the crystal nuclei, and reduce the fluctuation range of the half-peak width of the finished product.

[0032] High-temperature precise temperature control sintering: The pre-sintered product is heated to 620~700 ℃ and sintered at a constant temperature for 4~8 h; the sintering temperature and holding time are coordinated to regulate the degree of cell growth, and finally the target doped lithium iron phosphate cathode material is obtained.

[0033] In one embodiment, in the X-ray diffraction pattern of the metal ion-doped lithium iron phosphate active material, the offset Δ2θ of the (020) crystal plane corresponding to the 2x diffraction angle is 0.10°~0.25°, and the full width at half maximum (FWHM) value of the (020) crystal plane is 0.135°~0.170°.

[0034] In this embodiment, X-ray diffraction (XRD) refers to the characterization method of generating diffraction patterns by irradiating crystal materials with X-rays, which is used to analyze structural information such as crystal phase, interplanar spacing, and grain size. (020) Crystal plane refers to the characteristic crystal plane in the lithium iron phosphate olivine structure corresponding to the b-axis direction, which is the main channel for lithium ions to diffuse in and out of the crystal lattice.

[0035] In one embodiment, the relationship between the offset of twice the diffraction angle of the (020) crystal plane and the full width at half maximum (FWHM) value satisfies the first formula: S=Δ2θ×FWHM Where S ranges from 0.015 to 0.040, Δ2θ is the offset of twice the diffraction angle of the (020) crystal plane, and FWHM is the half-width at half maximum (WHM) value of the (020) crystal plane.

[0036] In this embodiment, S is a comprehensive parameter obtained by multiplying the offset of twice the diffraction angle of the (020) crystal plane by the half-peak width value. It is used to quantify the degree of lattice distortion and channel transport efficiency of the crystal plane and is a related index for evaluating the lithium-ion migration rate.

[0037] In a specific embodiment: Example 2: S = 0.12 × 0.155 ≈ 0.0186; Example 3 (Magnesium-Titanium Co-doping): S = 0.14 × 0.161 ≈ 0.0225; Example 5: S = 0.22 × 0.158 ≈ 0.0347; When S is in a specific lattice distortion range of 0.015-0.040, the interplanar spacing and transmission channels are optimally controlled, and its 10C high-rate discharge specific capacity (65.32~75.96 mAh / g) shows a nonlinear jump and abrupt change compared to the comparative example (undoped, 10C capacity is only 59.63 mAh / g).

[0038] In one embodiment, the iron source Fe is selected from one or more of iron phosphate, iron acetate, iron oxide, iron citrate, and ferrous oxalate; the phosphorus source P is selected from one or more of phosphoric acid, ammonium phosphate, and ammonium dihydrogen phosphate; the lithium source Li is selected from one or more of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate; the doping element source M is a compound containing at least one of Ti, Mg, Zr, Cr, and Nb; and the carbon source C is selected from one or more of glucose, sucrose, maltose, graphite, carbon nanotubes, graphene, and polyethylene glycol.

[0039] In one embodiment, in S11, the drying temperature is 60°C to 120°C; the temperature of the low-temperature section of the segmented sintering process is 350°C to 420°C, the temperature of the high-temperature section is 620°C to 700°C, and the sintering reaction time is 2h to 8h.

[0040] Low-temperature pre-crystallization treatment: The precursor powder is pre-calcined at 350-420 °C for 2-3 h under a protective atmosphere to initially form olivine crystal nuclei, pre-regulate the basic size of the crystal nuclei, and reduce the fluctuation range of the half-peak width of the finished product.

[0041] High-temperature precision temperature control sintering: heating to 620-700 ℃ and sintering at a constant temperature for 4-8 h; sintering temperature and holding time synergistically regulate cell growth: increasing sintering temperature and extending holding time will increase grain size and narrow the half-peak width; decreasing sintering temperature and shortening holding time will refine grain size and increase the half-peak width; by combining the type and amount of dopant ions, the Δ2θ offset is precisely controlled to fall within the range of 0.10° to 0.25°, and the half-peak width falls within the range of 0.135° to 0.170°.

[0042] The carbon source mixed precursor powder is subjected to low-temperature and high-temperature heat treatment to form a conductive carbon coating layer on the particle surface, and finally the target doped lithium iron phosphate cathode material is obtained.

[0043] In one embodiment, the conductive agent is selected from carbon black, conductive graphite, carbon fiber, graphene, and carbon nanotubes.

[0044] See Figure 2 , Figure 2 This is a schematic flowchart illustrating a method for preparing a lithium-ion battery according to an embodiment of the present invention. The method for preparing the lithium-ion battery includes the following steps S21-S22.

[0045] S21, the negative electrode active material is mixed evenly with binder and conductive agent to prepare negative electrode slurry; the negative electrode slurry is coated on the surface of current collector, and then dried and rolled to obtain negative electrode sheet.

[0046] S22, the positive electrode sheet prepared by the method for preparing a doped lithium iron phosphate positive electrode with quantitative control of XRD diffraction characteristics as described in any of the above embodiments is assembled with the negative electrode sheet to form a battery cell. The battery cell is then packaged after hot pressing to obtain a lithium-ion battery.

[0047] In one embodiment, the negative electrode active material is selected from graphite, nano-silicon, and lithium titanate.

[0048] In one embodiment, see Figure 3 The preparation method of this lithium-ion battery also includes the following testing steps S31-S33: S31, after charging at a preset rate with constant current to the charging cutoff voltage, switches to constant voltage charging, and then rests after the charging current drops to the cutoff current.

[0049] S32 discharges at a preset discharge rate with constant current until the discharge cutoff voltage is reached, then allows it to stand still.

[0050] S33, steps S31-S32 are executed repeatedly using multiple different discharge rates.

[0051] In a specific embodiment, the rate performance of the prepared lithium-ion battery is tested, and the example process is as follows: At 25℃, charge at a constant current rate of 1C to 3.65V, then switch to constant voltage charging at 3.65V until the charging current drops to 0.02C. After charging is complete, let stand for 5 minutes.

[0052] Discharged sequentially at constant current rates of 1C, 2C, 5C, and 10C to 2.5V. The charging and resting steps were repeated before each discharge rate test. The corresponding discharge specific capacity was recorded after each discharge stage.

[0053] This testing method can obtain discharge capacity data at different rates, which can be used to quantitatively evaluate the rate performance of cathode materials.

[0054] The following provides a comparative example 1 and experimental examples 1-8 for the preparation method of lithium-ion batteries: Example 1 Weigh 1 mole of ferrous oxalate and 1 mole of phosphoric acid, add 1.05 moles of lithium hydroxide monohydrate, 0.01 moles of magnesium acetate, and 10% glucose, and mix for 1 hour. Transfer the resulting slurry to a sand mill and grind for 2 hours. Remove the slurry and dry it at 80°C. Transfer the dried material to a calcining furnace and sinter it under a nitrogen protective atmosphere at 650°C for 8 hours. Crush and sieve the sintered material using a vibrating screen to obtain doped lithium iron phosphate.

[0055] Lithium iron phosphate material, binder (PVDF), conductive carbon black are mixed and formulated into a slurry, which is then coated onto aluminum foil, dried, and rolled to obtain the positive electrode sheet. The negative electrode active material (artificial graphite), binder (CMC), and conductive carbon black are mixed and formulated into a slurry, which is then coated onto copper foil, dried, and rolled to obtain the negative electrode sheet. Positive and negative electrode sheets are assembled into a cell, and the cell is then hot-pressed and packaged to obtain a full cell.

[0056] The powder resistivity and 2.5-3.65V rate capability of this material are as follows: Figure 4 As shown, the XRD (020) peak lattice parameters are as follows: Figure 5 As shown.

[0057] Example 2 The difference from Example 1 is that the molar amount of magnesium acetate added is 0.03.

[0058] Example 3 The difference from Example 2 is that 0.015 moles of nano-titanium dioxide are added as a common metal ion dopant.

[0059] Example 4 The difference from Example 1 is the addition of 0.02 moles of nano-titanium dioxide as a metal ion dopant.

[0060] Example 5 The difference from Example 4 is that 0.02 moles of niobium pentoxide are added as a common metal ion dopant.

[0061] Example 6 The difference from Example 5 is that the sintering process is divided into low temperature and high temperature treatment. The dried slurry is first sintered at 380°C for 2 hours under a nitrogen protective atmosphere, and then the temperature is further increased to 650°C for 6 hours.

[0062] Example 7 The difference from Example 6 is that the high-temperature sintering temperature is 650°C and the sintering time is 10 hours.

[0063] Example 8 The difference from Example 6 is that the high-temperature sintering temperature is 650°C and the sintering time is 3 hours.

[0064] Comparative Example 1 Weigh 1 mole of ferrous oxalate and 1 mole of phosphoric acid, add 1.05 moles of lithium hydroxide monohydrate and 10% glucose, and mix for 1 hour. Transfer the resulting slurry to a sand mill and grind for 2 hours. Remove the slurry and dry it at 80°C. Transfer the dried material to a calcining furnace and sinter it under a nitrogen protective atmosphere at 650°C for 8 hours. Crush and sieve the sintered material using a vibrating screen to obtain doped lithium iron phosphate.

[0065] Lithium iron phosphate material, binder (PVDF), conductive carbon black are mixed and formulated into a slurry, which is then coated onto aluminum foil, dried, and rolled to obtain the positive electrode sheet. The negative electrode active material (artificial graphite), binder (CMC), and conductive carbon black are mixed and formulated into a slurry, which is then coated onto copper foil, dried, and rolled to obtain the negative electrode sheet. Positive and negative electrode sheets are assembled into a cell, and the cell is then hot-pressed and packaged to obtain a full cell.

[0066] The powder resistivity and 2.5-3.65V rate capability of this material are as follows: Figure 4 As shown, the XRD (020) peak lattice parameters are as follows: Figure 5 As shown.

[0067] To further illustrate the embodiments of the present invention, the specific capacity test and X-ray diffraction spectroscopy test conditions for all the above embodiments are as follows: Specific capacity test: 1C constant current charging to 3.65V, 3.65V constant voltage charging to the current drop to 0.02C; let stand for 5 minutes; 1C discharge to 2.5V and let stand for 5 minutes; repeat the above constant current and constant voltage charging steps, and discharge to 2.5V at 2C, 5C and 10C respectively.

[0068] X-ray diffraction spectroscopy test: The test was conducted using a fully automated X-ray powder line diffractometer.

[0069] Compared with Comparative Example 1, Examples 1-2 show that adding appropriate equivalent magnesium ions improves electronic conductivity and specific capacity at different doping rates. Example 1 has a low doping concentration, Δ2θ < 0.10°, and exhibits significant lattice defects due to control failure.

[0070] Compared with Comparative Example 1, Examples 3-5 show that adding a certain proportion of high-valence titanium or niobium ions increases the offset of the (020) crystal plane in the lattice by twice the diffraction angle, reduces the half-peak width, increases the interplanar spacing, increases the ionic conductivity, enables lithium ions to be transported quickly in the lattice, and improves the rate performance.

[0071] Examples 6-8 involved low-temperature and high-temperature sintering, respectively. While the diffraction shift range was met, the full width at half maximum (FWHM) was below 0.10° (Example 8), resulting in abnormal grain growth, a longer lithium-ion diffusion path, and poor high-rate performance. In Example 7, the FWHM was above 0.25°, leading to poor crystal order, increased charge transfer impedance, and a decline in both capacity and rate of increase. Only by simultaneously limiting the coupling window between the XRD diffraction angle shift and the main peak FWHM can the synergistic optimization of lattice channels, grain size, and lattice strain be achieved, resulting in unexpected comprehensive electrochemical performance and validating the inventiveness and necessity of the present invention.

[0072] In the above embodiments, the descriptions of each embodiment have different focuses. For parts that are not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.

[0073] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Since these modifications and variations fall within the scope of the claims and their equivalents, this invention also intends to include these modifications and variations.

[0074] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a lithium iron phosphate cathode with quantitatively controlled XRD diffraction characteristics, characterized in that, The method includes the following steps: S11, according to the chemical formula Li x M y FePO4 is prepared by mixing lithium (Li), iron (Fe), phosphorus (P), carbon (C), and dopant element (M) in deionized water and grinding to obtain a slurry. The slurry is then dried and sintered in stages under an inert atmosphere. The sintered product is then sieved to obtain metal ion-doped lithium iron phosphate active material. Here, x ranges from 0.95 to 0.995, y ranges from 0.005 to 0.05, and the dopant element M is selected from one or more metal ions chosen from Ti, Mg, Zr, Cr, and Nb. S12. Mix the metal ion-doped lithium iron phosphate active material with binder and conductive agent evenly to prepare a positive electrode slurry. S13. The positive electrode slurry is coated on the surface of the current collector, and then dried and rolled to obtain a lithium iron phosphate positive electrode sheet.

2. The method according to claim 1, characterized in that, In the X-ray diffraction pattern of the metal ion-doped lithium iron phosphate active material, the offset Δ2θ of the (020) crystal plane corresponding to the 2x diffraction angle is 0.10°~0.25°, and the full width at half maximum (FWHM) value of the (020) crystal plane is 0.135°~0.170°.

3. The method according to claim 2, characterized in that, The relationship between the offset of twice the diffraction angle of the (020) crystal plane and the full width at half maximum (FWHM) value satisfies the first formula: S=Δ2θ×FWHM Where S ranges from 0.015 to 0.040, Δ2θ is the offset of twice the diffraction angle of the (020) crystal plane, and FWHM is the half-width at half maximum (WHM) value of the (020) crystal plane.

4. The method according to claim 1, characterized in that, The iron source Fe is selected from one or more of ferric phosphate, ferric acetate, ferric oxide, ferric citrate, and ferrous oxalate; The phosphorus source P is selected from one or more of phosphoric acid, ammonium phosphate, and ammonium dihydrogen phosphate; The lithium source Li is selected from one or more of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate; The doping element source M is a compound containing at least one element selected from Ti, Mg, Zr, Cr, and Nb; The carbon source C is selected from one or more of glucose, sucrose, maltose, graphite, carbon nanotubes, graphene, and polyethylene glycol.

5. The method according to claim 1, characterized in that, In S11, the drying temperature is 60℃~120℃; the temperature of the low-temperature section of the segmented sintering process is 350℃~420℃, the temperature of the high-temperature section is 620℃~700℃, and the sintering reaction time is 2h~8h.

6. The method according to claim 1, characterized in that, The current collector is aluminum foil.

7. The method according to claim 1, characterized in that, The conductive agent is selected from one or more of carbon black, conductive graphite, carbon fiber, graphene, and carbon nanotubes.

8. A method for preparing a battery, characterized in that, Includes the following steps: S21. Mix the negative electrode active material with the binder and conductive agent evenly to prepare a negative electrode slurry; coat the negative electrode slurry onto the surface of the current collector, and then dry and roll-press it to obtain a negative electrode sheet. S22. The positive electrode sheet prepared by the method for preparing lithium iron phosphate positive electrode with quantitatively controlled XRD diffraction characteristics as described in any one of claims 1-7 is assembled with the negative electrode sheet to form a battery cell. The battery cell is then hot-pressed and packaged to obtain a lithium-ion battery.

9. The method according to claim 8, characterized in that, The negative electrode active material is selected from one of graphite, nano-silicon, and lithium titanate.

10. The method according to claim 8, characterized in that, It also includes testing steps for the resulting lithium-ion batteries: S31. Charge at a preset rate with constant current until the charging cutoff voltage is reached, then switch to constant voltage charging. Let it stand after the charging current drops to the cutoff current. S32. Discharge at a constant current at a preset discharge rate until the discharge cutoff voltage is reached, then let stand still. S33. Repeat steps S31-S32 sequentially using multiple different discharge rates.